Use of accelerator and conductive additive in preparing low-temperature conductive copper paste and low-temperature conductive copper paste

By using bifunctional group urea accelerator and imidazole conductive additives in copper slurry, the problems of low solid content and high temperature curing of copper slurry are solved, low temperature curing and high conductivity are achieved, and storage stability and adhesion are improved.

CN116959778BActive Publication Date: 2024-12-31LONGI GREEN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310806692.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2024-12-31
Estimated Expiration
2043-07-03

AI Technical Summary

Technical Problem

The existing copper slurry has low solid content and high temperature curing, which cannot meet the high conductivity requirements and long-term storage requirements.

Method used

Mono-substituted urea or disubstituted urea containing difunctional groups is used as accelerator and imidazole sulfonate, imidazole phosphate or imidazole acetate as conductive additives to reduce the curing temperature of the copper slurry and improve the efficiency of the conductive channel.

Benefits of technology

Low temperature curing and high conductivity are achieved, contact resistance and resistivity are reduced, storage stability and adhesion are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004322767730000091
    Figure BDA0004322767730000091
  • Figure BDA0004322767730000092
    Figure BDA0004322767730000092
  • Figure BDA0004322767730000131
    Figure BDA0004322767730000131
Patent Text Reader

Abstract

The present application discloses a promoter and a conductive auxiliary agent for use in preparing a low-temperature conductive copper paste and a low-temperature conductive copper paste, wherein the promoter is a monosubstituted urea or a disubstituted urea containing a bifunctional group, and the conductive auxiliary agent is an imidazole sulfonate, an imidazole phosphate or an imidazole acetate. The promoter is used in the low-temperature conductive copper paste to promote the reaction of the polymer resin and the low-activity curing agent in the copper paste, thereby reducing the curing temperature of the copper paste, so that the low-temperature conductive copper paste can be cured at low temperatures, and has good storage stability and low contact resistance. The conductive auxiliary agent used in the present application is used in the low-temperature conductive copper paste, and will produce a good conductive channel with ITO and TCO, thereby greatly reducing the contact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of copper paste, and in particular to the use of a promoter and a conductive additive in the preparation of a low-temperature conductive copper paste and the low-temperature conductive copper paste. Background Art

[0002] Compared with conductive silver paste, copper paste is increasingly valued by various industries due to its low cost and high conductivity. Currently, the existing copper paste has the following problems:

[0003] 1. Low solid content of copper powder: Since nano copper powder must be surface treated, the tap density is small, and the preparation of slurry requires more organic phase wetting and dispersion, so the solid content is limited. At present, the solid content of copper powder in the existing technology does not exceed 90%, and is generally below 85%, so the square resistance is large and cannot meet the application occasions requiring high conductivity.

[0004] 2. High temperature curing: Since copper has high catalytic activity at the nanoscale, even after surface passivation treatment, it still has a certain catalytic activity, which will accelerate the curing reaction of the organic phase, such as catalyzing the curing reaction of epoxy resin and acid anhydride, and the curing reaction of epoxy resin and imidazole. Therefore, copper paste with high reactive resin and curing agent will have a slow gel reaction in a short period of time and a short storage period. In order to enable long-term storage and continuous printing, a low-activity curing system or a low-reactive polymer resin is generally selected, resulting in the need for curing at a higher temperature. Summary of the invention

[0005] In view of the above technical problems, the present application provides a promoter and a conductive auxiliary agent for use in preparing a low-temperature conductive copper paste and a low-temperature conductive copper paste. The promoter is used in the low-temperature conductive copper paste to promote the reaction of the polymer resin and the low-activity curing agent in the copper paste, thereby reducing the curing temperature of the copper paste, so that the low-temperature conductive copper paste can be cured at low temperatures, and has good storage stability and low contact resistance. The conductive auxiliary agent used in the present application is used in the low-temperature conductive copper paste, and will produce a good conductive channel with ITO and TCO, thereby greatly reducing the contact resistance.

[0006] The specific technical solutions of this application are as follows:

[0007] The present application provides the use of an accelerator in preparing a low-temperature conductive copper paste, wherein the accelerator is a monosubstituted urea or a disubstituted urea containing a bifunctional group.

[0008] Preferably, for the above-mentioned use, the accelerator is DYHARD UR400 or DYHARDUR500.

[0009] Preferably, for the above-mentioned use, the content of the accelerator in the low-temperature conductive copper paste is 0.15-0.45%.

[0010] The present application provides the use of a conductive aid in preparing a low-temperature conductive copper paste, wherein the conductive aid is an imidazole sulfonate, an imidazole phosphate or an imidazole acetate.

[0011] Preferably, for the above-mentioned use, the content of the conductive additive in the low-temperature conductive copper paste is 0.05-0.20%.

[0012] The present application provides a low-temperature conductive copper paste, wherein the low-temperature conductive copper paste contains an accelerator, and the accelerator is a monosubstituted urea or a disubstituted urea containing a bifunctional group.

[0013] Preferably, for the low-temperature conductive copper paste described above, the accelerator is DYHARD UR400 or DYHARD UR500.

[0014] Preferably, for the low-temperature conductive copper paste described above, the accelerator is 0.15-0.45% by mass in the low-temperature conductive copper paste.

[0015] Preferably, for the low-temperature conductive copper paste described above, the low-temperature conductive copper paste contains a conductive additive, and the conductive additive is imidazole sulfonate, imidazole phosphate or imidazole acetate.

[0016] Preferably, for the low-temperature conductive copper paste described above, the conductive additive accounts for 0.05-0.20% by mass in the low-temperature conductive copper paste.

[0017] Preferably, for the low-temperature conductive copper paste described above, the low-temperature conductive copper paste further comprises copper powder, polymer resin, solvent, curing agent, dispersant, coupling agent and thixotropic agent;

[0018] Preferably, in terms of mass percentage in the low-temperature conductive copper paste,

[0019] The copper powder is 86-92%;

[0020] The polymer resin is 1-3%;

[0021] The solvent is 4-8%;

[0022] The curing agent is 0.5-1.5%;

[0023] The dispersant is 0.2-1%;

[0024] The coupling agent is 0.2-0.5%;

[0025] The thixotropic agent is 0.01-0.05%.

[0026] Preferably, for the low-temperature conductive copper paste described above, wherein the polymer resin comprises a main resin and an auxiliary resin, preferably, the main resin is selected from one or more of hydrogenated bisphenol A epoxy resin, polyurethane-modified epoxy resin, dimer acid-modified epoxy resin and siloxane-modified epoxy resin;

[0027] And / or, the auxiliary resin is an aldehyde-ketone resin.

[0028] Preferably, for the low-temperature conductive copper paste described above, the main resin accounts for 60-90% and the auxiliary resin accounts for 10-40% by mass in the polymer resin.

[0029] Preferably, for the low-temperature conductive copper paste described above, the copper powder comprises micron-sized flaky copper powder and nano-sized spherical copper powder;

[0030] Preferably, in terms of mass percentage in the copper powder, the micron-sized flaky copper powder accounts for 30-50%, and the nano-sized spherical copper powder accounts for 50-70%.

[0031] Preferably, for the low-temperature conductive copper paste described above, the solvent is selected from one or more of dibasic acid ester (DBE), diethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, diethylene glycol butyl ether acetate and terpineol.

[0032] Preferably, for the low-temperature conductive copper paste described above, the curing agent is selected from one or more of Trixene BI 7982, MF-K60X, ketoxime-terminated isocyanate, hexanethiol-terminated hexamethylene diisocyanate, and dodecyl mercaptan-terminated diphenyl diisocyanate;

[0033] and / or, the dispersant is selected from one or more of BYK-108, BYK-110, BYK-111, Tween 80, oleic acid, oleylamine and triethyl phosphate;

[0034] And / or, the coupling agent is an organosilicon coupling agent and / or a titanate coupling agent, preferably, the organosilicon coupling agent is KH-560 and / or KH-570, preferably, the titanate coupling agent is selected from one or more of isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl tri(dioctyl pyrophosphate) titanate and isopropyl tri(dioctyl phosphate) titanate;

[0035] And / or, the thixotropic agent is polyamide wax, polyoxyethylene castor oil, hydrophobic gas silicone or BYK-405.

[0036] The present application provides the use of a low-temperature conductive copper paste in a perovskite battery, wherein the low-temperature conductive copper paste is used to make electrodes of the perovskite battery, and the low-temperature conductive copper paste is the low-temperature conductive copper paste described above.

[0037] Effects of the Invention

[0038] The present application uses a monosubstituted urea or disubstituted urea containing a bifunctional group as an accelerator, which has stable performance below the deblocking temperature, will not be catalyzed by nano-copper, has low reactivity with polymer resin, and is stable in storage. At 130°C, it will quickly catalyze the reaction between the polymer resin and the low-activity curing agent, thereby reducing the curing temperature of the conductive copper paste.

[0039] The conductive additives (e.g., 1-ethyl-3-methylimidazolium methanesulfonate, 1-ethyl-3-methylimidazolium acetate) used in this application belong to ionic liquids, which are organic electrolytes, similar to inorganic electrolyte solutions, and free-moving ions are driven by the potential gradient in the electric field to spontaneously produce directional movement to achieve conductivity. At the same time, studies have shown that in addition to the ionic mechanism, conductive additives such as imidazolium salts can also carry current through the directional movement of the molecules themselves. As a conductive additive for preparing low-temperature conductive copper paste, it will produce a good conductive channel with ITO and TCO, thereby greatly reducing the contact resistance.

[0040] The low-temperature conductive copper paste described in the present application can reduce the resistivity to below 30 μΩ·cm and the contact resistance to below 8Ω under the conditions of 130°C and 10 minutes of nitrogen atmosphere curing, and can achieve good adhesion and excellent ohmic contact performance on ITO or TCO substrates, good storage stability, low contact resistance and resistivity, and good adhesion on both ITO and TCO surfaces. DETAILED DESCRIPTION

[0041] The present application is described in detail below in conjunction with the described embodiments. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to enable the scope of the present application to be fully communicated to those skilled in the art.

[0042] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the functional differences of components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.

[0043] The present application provides the use of an accelerator in preparing a low-temperature conductive copper paste, wherein the accelerator is a monosubstituted urea and / or a disubstituted urea containing a bifunctional group.

[0044] In the present application, the monosubstituted urea containing a bifunctional group refers to a urea group in which one of the two hydrogen atoms on a nitrogen atom is replaced by another functional group. Similarly, the disubstituted urea refers to a urea group in which both hydrogen atoms on a nitrogen atom are replaced by another functional group.

[0045] The accelerator described in the present application is a blocked monosubstituted urea and disubstituted urea containing a bifunctional group, with a minimum deblocking temperature of 80°C, stable properties, and can be stably stored at room temperature for more than 6 months. It has high activity after deblocking and can promote a rapid reaction between the curing agent and the epoxy resin, so that the slurry can be completely cured within 10 minutes at a relatively low temperature, such as 130°C.

[0046] In some embodiments, the accelerator is DYHARD UR400 or DYHARD UR500. In some embodiments, the content of the accelerator in the low-temperature conductive copper paste is 0.15-0.45%.

[0047] For example, the content of the accelerator in the low-temperature conductive copper paste may be 0.15%, 0.20%, 0.25%, 0.35%, 0.40%, 0.45%, etc.

[0048] The chemical formula of DYHARD UR400 is H3C-C6H4-NH-CO-N(CH3)2.

[0049] The chemical formula of DYHARD UR500 is H3C-C6H3[NH-CO-N(CH3)2]2.

[0050] The accelerator described in the present application has good storage stability and reactivity, and a relatively small amount of addition can meet the curing requirements.

[0051] The present application provides a use of a conductive aid in preparing a low-temperature conductive copper paste, wherein the conductive aid is an imidazole sulfonate, an imidazole phosphate or an imidazole acetate, preferably, the imidazole sulfonate is 1-ethyl-3-methylimidazolium methane sulfonate;

[0052] Preferably, the imidazole phosphate salt is 1-butyl-3-methylimidazole dibutyl phosphate salt;

[0053] Preferably, the imidazole acetate is 1-ethyl-3-methylimidazolium acetate.

[0054] The conductive additive described in the present application forms a molecular-level connection path between the copper powder and the conductive base layer. The amines (NH, NH2) in the conductive additive have good complexing ability with ITO and TCO.

[0055] In some embodiments, the content of the conductive additive in the low-temperature conductive copper paste is 0.05-0.20%.

[0056] For example, the content of the conductive additive in the low-temperature conductive copper paste can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, etc.

[0057] The present application uses imidazole sulfonate, imidazole phosphate or imidazole acetate as a conductive additive, which can achieve ionic conductivity of organic materials, and has good complexing force with ITO (TCO), providing a good conductive channel, thereby greatly reducing contact resistance.

[0058] The present application provides a low-temperature conductive copper paste, wherein the low-temperature conductive copper paste contains an accelerator, and the accelerator is a monosubstituted urea or a disubstituted urea containing a bifunctional group. In some embodiments, the accelerator is DYHARDUR400 or DYHARD UR500. In some embodiments, the accelerator is 0.15-0.45% by mass percentage in the low-temperature conductive copper paste.

[0059] For example, the accelerator may be 0.15%, 0.20%, 0.25%, 0.35%, 0.40%, 0.45%, etc., in terms of mass percentage in the low-temperature conductive copper paste.

[0060] The low-temperature conductive copper paste described in the present application contains a promoter, which is a closed type, stable in nature, can be stably stored at room temperature, and has high activity after unblocking, which can promote the rapid reaction of the curing agent and realize the rapid curing of the slurry within 10 minutes at a lower temperature, for example, at 130°C. Since perovskite is an ionic crystal material, it is more fragile and less stable than crystalline silicon. High temperature can easily lead to thermal expansion, phase change, oxidation or acceleration of other kinetic processes of perovskite materials, resulting in serious efficiency decay. Low-temperature short-time curing can effectively reduce the efficiency decay of perovskite cells. The low-temperature conductive copper paste of the present application is preferably suitable for making electrodes for perovskite cells.

[0061] In some embodiments, the low-temperature conductive copper paste contains a conductive additive, and the conductive additive is imidazole sulfonate, imidazole phosphate or imidazole acetate. Preferably, the imidazole sulfonate is 1-ethyl-3-methylimidazolium methane sulfonate; preferably, the imidazole phosphate is 1-butyl-3-methylimidazolium dibutyl phosphate; preferably, the imidazole acetate is 1-ethyl-3-methylimidazolium acetate. In some embodiments, the conductive additive is 0.05-0.20% by mass in the low-temperature conductive copper paste.

[0062] For example, in terms of mass percentage in the low-temperature conductive copper paste, the conductive aid can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, etc.

[0063] The conductive additive has good dispersibility and good complexing ability with ITO and TCO, and can generate good conductivity through directional arrangement, thereby providing a good conductive path for copper powder and ITO (TCO).

[0064] In some embodiments, the low-temperature conductive copper paste further comprises copper powder, polymer resin, solvent, curing agent, dispersant and thixotropic agent;

[0065] Preferably, the copper powder is 86-92% by mass in the low-temperature conductive copper paste;

[0066] The polymer resin is 1-3%;

[0067] The solvent is 4-8%;

[0068] The curing agent is 0.5-1.5%;

[0069] The dispersant is 0.2-1%;

[0070] The coupling agent is 0.2-0.5%;

[0071] The thixotropic agent is 0.01-0.05%.

[0072] For example, the powder may be 86%, 87%, 88%, 89%, 90%, 91%, 92%, etc., in terms of mass percentage in the low-temperature conductive copper paste;

[0073] The polymer resin may be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, etc.;

[0074] The solvent can be 4%, 5%, 6%, 7%, 8%, etc.;

[0075] The curing agent can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.;

[0076] The dispersant may be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc.;

[0077] The coupling agent can be 0.2%, 0.3%, 0.4%, 0.5%, etc.;

[0078] The thixotropic agent is 0.01%, 0.02%, 0.03%, 0.04%, 0.05% and the like.

[0079] In some embodiments, the polymer resin comprises a main resin and an auxiliary resin. Preferably, the main resin is selected from one or more of hydrogenated bisphenol A epoxy resin, polyurethane modified epoxy resin, dimer acid modified epoxy resin and siloxane modified epoxy resin; preferably, the auxiliary resin is an aldehyde ketone resin.

[0080] In the present application, the epoxy equivalent of the main resin is not less than 200, and the viscosity is not higher than 5000 cps.

[0081] In the present application, aldehyde-ketone resin is used as an auxiliary resin and combined with the main resin to form a polymer resin. The saturated ring structure of the aldehyde-ketone resin gives it good hardness, heat resistance, degradation resistance and weather resistance; the large number of ketone groups and hydroxyl groups on the molecular chain give it good adhesion on the ITO and TCO surfaces; in addition, the main resin used is a low-viscosity modified epoxy resin, which ensures that the slurry with a high solid content can also have a lower viscosity, ensuring good printing performance.

[0082] In some embodiments, the main resin accounts for 60-90% and the auxiliary resin accounts for 10-40% by mass in the polymer resin.

[0083] For example, in terms of mass percentage in the polymer resin, the main resin is 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc.; the auxiliary resin can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc.

[0084] In some embodiments, the copper powder comprises micron-sized flaky copper powder and nano-sized spherical copper powder;

[0085] Preferably, in terms of mass percentage in the copper powder, the micron-sized flaky copper powder accounts for 30-50%, and the nano-sized spherical copper powder accounts for 50-70%.

[0086] For example, the micron-sized flaky copper powder may be 30%, 35%, 40%, 45%, 50%, etc., in terms of mass percentage in the copper powder;

[0087] The nano-scale spherical copper powder may be 50%, 55%, 60%, 65%, 70%, etc.

[0088] In the present application, the particle size D50 of the micron-sized flaky powder is less than 4 μm; the particle size D50 of the nano-sized spherical powder is less than 200 nm.

[0089] This application uses nano-scale spherical copper powder, which can be filled into the gaps where the flaky copper powder is accumulated, improving the conductivity of the slurry; at the same time, the thixotropy of the slurry is increased, and a full and flat line shape is obtained when printing fine grid lines. At the same time, for velvet or rough surfaces, nano-spherical copper powder is easier to fill into the pores, increasing the contact area between the slurry and ITO or TCO, thereby reducing the contact resistance.

[0090] The copper powder described in the present application is a copper powder commonly used in the art that has undergone surface passivation treatment. The copper powder can be treated by conventional methods in the art, for example, the copper powder can be treated by the following methods:

[0091] 1. Use strong acid such as dilute sulfuric acid and dilute hydrochloric acid to remove the surface oxide layer of micro-nano copper powder.

[0092] 2. Use alcohol to wash away strong acid and organic impurities on the surface of micro-nano copper powder.

[0093] 3. Weigh a certain amount of formic acid and the cleaned copper powder in a molar ratio, disperse them in an ethanol solution, and react them in a high-temperature water bath to obtain formic acid-coated micro-nano copper powder.

[0094] 4. Use oleic acid, oleylamine, linoleic acid and other compounds as coating agents, dissolve them in ethanol solution, and place them in a high-temperature and high-pressure reactor with the obtained formic acid-coated micro-nano copper powder. Heat and react for 10 hours with nitrogen to obtain micro-nano copper powder coated with different substances such as oleic acid formic acid, oleylamine formic acid, and linoleic acid formic acid.

[0095] In some embodiments, the solvent is selected from one or more of dibasic acid ester (DBE), diethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, diethylene glycol butyl ether acetate and terpineol.

[0096] In some embodiments, the curing agent is selected from one or more of Trixene BI 7982, MF-K60X, ketoxime blocked isocyanate, hexanethiol blocked hexamethylene diisocyanate, and dodecyl mercaptan blocked diphenyl diisocyanate;

[0097] The dispersant is selected from one or more of BYK-108, BYK-110, BYK-111, Tween 80, oleic acid, oleylamine and triethyl phosphate;

[0098] The coupling agent is an organosilicon coupling agent and / or a titanate coupling agent. Preferably, the organosilicon coupling agent is KH-560 and / or KH-570. Preferably, the titanate coupling agent is selected from one or more of isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and isopropyl tri(dioctyl phosphate acyloxy) titanate.

[0099] The thixotropic agent is polyamide wax, polyoxyethylene castor oil, hydrophobic gas silicone or BYK-405.

[0100] In this application, Trixene BI 7982 refers to a blocked isocyanate based on hexamethylene diisocyanate solvent.

[0101] MF-K60X refers to a low-temperature blocked curing agent from Asahi Chemical of Japan, which is an aliphatic polyisocyanate based on hexamethylene diisocyanate.

[0102] Other curing agents can be obtained from the market or prepared by conventional methods in the art.

[0103] For example, for hexanethiol-terminated isophorone diisocyanate, it can be synthesized using the following reaction equation:

[0104]

[0105] For hexyl mercaptan-terminated diphenyl diisocyanate, it can be synthesized using the following reaction equation:

[0106]

[0107] In the present application, the oleylamine refers to cis-oleyl primary amine, namely 9-octadeceneamine.

[0108] In the present application, the preparation method of the low-temperature conductive copper paste is not limited in any way. The low-temperature conductive copper paste can be prepared by conventional methods in the art. For example, the method includes:

[0109] The main resin, the auxiliary resin and the solvent are mixed to obtain a polymer resin solution;

[0110] Adding a dispersant, a curing agent, a thixotropic agent, a coupling agent, a promoter, an optional conductive additive and copper powder into a polymer resin solution and mixing to obtain a premix;

[0111] The premix is ​​ground to obtain a low-temperature conductive copper slurry.

[0112] In the present application, optional means that the conductive aid may or may not be present.

[0113] That is, the method may include:

[0114] The main resin, the auxiliary resin and the solvent are mixed to obtain a polymer resin solution;

[0115] Adding a dispersant, a curing agent, a thixotropic agent, a coupling agent, an accelerator and copper powder into a polymer resin solution and mixing to obtain a premix;

[0116] The premix is ​​ground to obtain a low-temperature conductive copper slurry.

[0117] Alternatively the method may include:

[0118] The main resin, the auxiliary resin and the solvent are mixed to obtain a polymer resin solution;

[0119] Adding a dispersant, a curing agent, a thixotropic agent, a coupling agent, a accelerator, a conductive additive and copper powder into a polymer resin solution and mixing to obtain a premix;

[0120] The premix is ​​ground to obtain a low-temperature conductive copper slurry.

[0121] In some embodiments, the method comprises:

[0122] The aldehyde-ketone resin is dissolved in a mixed solvent to obtain a solution containing the aldehyde-ketone resin, and then the main resin and the solvent are added and mixed to obtain a polymer resin solution;

[0123] The dispersant is added to the polymer resin solution and stirred, and then a curing agent, a thixotropic agent, a accelerator and an optional conductive additive are added and mixed, and copper powder is added and premixed to obtain a premix;

[0124] The premix is ​​ground to obtain a low-temperature conductive copper slurry.

[0125] In some embodiments, the method comprises:

[0126] The aldehyde-ketone resin is mixed and dissolved with a mixed solvent of DBE and dipropylene glycol butyl ether to obtain a solution containing the aldehyde-ketone resin, and then the main resin and the solvent are added to mix to obtain a polymer resin solution, stirred and mixed, and filtered with a 400-600 mesh screen to remove impurities to obtain a polymer resin solution.

[0127] The dispersant is added to the polymer resin solution, and the mixture is fully stirred and dispersed. Then, a curing agent, an accelerator, a coupling agent, a thixotropic agent and an optional conductive additive are added to fully disperse the solution. Then, copper powder is added and the mixture is pre-mixed in a planetary mixer to obtain a premix.

[0128] The premix is ​​sheared and ground to obtain a low-temperature conductive copper slurry.

[0129] The low-temperature conductive copper paste described in this application can print a line width of 50μm; after curing at 130°C and 10 minutes in a nitrogen atmosphere, the resistivity can be reduced to 22μΩ·cm, and the contact resistance is less than 7Ω; the adhesion on ITO and TCO reaches 5B.

[0130] The present application provides the use of a low-temperature conductive copper paste in a perovskite battery, wherein the low-temperature conductive copper paste is used to make electrodes of the perovskite battery, and the low-temperature conductive copper paste is the low-temperature conductive copper paste described above.

[0131] Example

[0132] The present application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % means wt%, i.e., weight percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially.

[0133] Example 1 Preparation of copper paste

[0134] (1) 0.4 g of aldehyde-ketone resin was mixed with 0.4 g of a mixed solvent (DBE (60 wt%) and dipropylene glycol butyl ether (40 wt%)) to obtain 0.8 g of an aldehyde-ketone resin solution, and 1.6 g of a hydrogenated bisphenol A epoxy resin and 5.48 g of diethylene glycol butyl ether were added, stirred and mixed at room temperature, and then filtered through a 500-mesh sieve to remove impurities to obtain a polymer resin solution.

[0135] (2) 0.5 g of dispersant Tween 80 and 0.3 g of coupling agent KH-570 were added to the above polymer resin solution, and the mixture was stirred and dispersed uniformly. Then, 1 g of K60X, 0.3 g of accelerator DYHARD UR400, and 0.02 g of polyamide wax were added to the above solution and dispersed fully. Then, 45 g of nano-spherical copper powder and 45 g of flaky micron copper powder were added and premixed in a planetary mixer to obtain a premix.

[0136] (3) The obtained premix is ​​subjected to high-speed shear grinding in a three-roll mill to obtain a low-temperature conductive copper slurry, and the obtained slurry is passed through a 400-mesh sieve to remove impurities and large particles, and then vacuum degassing is performed to obtain a copper slurry.

[0137] Example 2 Preparation of copper paste

[0138] The difference between Example 2 and Example 1 is that in Example 2, 0.08 g of 1-ethyl-3-methylimidazole acetate is added.

[0139] Example 3 Preparation of copper paste

[0140] The difference between Example 3 and Example 1 is that in Example 3, 0.08 g of 1-butyl-3-methylimidazole dibutyl phosphate is added.

[0141] Example 4 Preparation of copper paste

[0142] The difference between Example 4 and Example 1 is that in Example 4, 0.08 g of 1-ethyl-3-methylimidazolium methanesulfonate is added.

[0143] Example 5 Preparation of copper paste

[0144] The difference between Example 5 and Example 3 is that in Example 5, 0.5 g of K60X curing agent is added.

[0145] Example 6 Preparation of copper paste

[0146] The difference between Example 6 and Example 3 is that in Example 6, 1.5 g of K60X curing agent is added.

[0147] Example 7 Preparation of copper paste

[0148] The difference between Example 7 and Example 3 is that the amount of the accelerator is 0.15 g.

[0149] Example 8 Preparation of copper paste

[0150] The difference between Example 8 and Example 3 is that the amount of the accelerator is 0.45 g.

[0151] Example 9 Preparation of copper paste

[0152] The difference between Example 9 and Example 3 is that the amount of flake powder added is 27g, and the amount of ball powder added is 63g.

[0153] Example 10 Preparation of copper paste

[0154] The difference between Example 10 and Example 3 is that the amount of flake powder added is 63g, and the amount of ball powder added is 27g.

[0155] Example 11 Preparation of copper paste

[0156] The difference between Example 11 and Example 3 is that the amount of epoxy resin added is 2.0 g, and the amount of aldehyde-ketone resin added is 0 g.

[0157] Example 12 Preparation of copper paste

[0158] The difference between Example 12 and Example 3 is that the amount of epoxy resin added is 0.5 g, and the amount of aldehyde-ketone resin added is 1.5 g.

[0159] Example 13 Preparation of copper paste

[0160] The difference between Example 13 and Example 3 is that the accelerator used in Example 13 is UR500.

[0161] Example 14 Preparation of copper paste

[0162] The difference between Example 14 and Example 3 is that the amount of epoxy resin added is 1.2 g, and the amount of aldehyde-ketone resin added is 0.8 g.

[0163] Example 15 Preparation of copper paste

[0164] The difference between Example 15 and Example 3 is that the amount of epoxy resin added is 1.8 g, and the amount of aldehyde-ketone resin added is 0.2 g.

[0165] Example 16 Preparation of copper paste

[0166] The difference between Example 16 and Example 3 is that the amount of the accelerator added in Example 16 is 0.08 g.

[0167] Example 17 Preparation of copper paste

[0168] The difference between Example 17 and Example 3 is that the added amount of the conductive aid is 0.05 g.

[0169] Example 18 Preparation of copper paste

[0170] The difference between Example 18 and Example 3 is that the added amount of the conductive aid is 0.2 g.

[0171] Comparative Example 1

[0172] The difference between Comparative Example 1 and Example 3 is that the accelerator is changed to imidazole, and the added amount remains unchanged.

[0173] Comparative Example 2

[0174] The difference between Comparative Example 2 and Example 3 is that no accelerator is added.

[0175] In order to better compare the effects of each component on the slurry properties, the above embodiments and comparative examples all ensure that the total mass remains unchanged, and the changes in the amount of each component added are controlled by adjusting the amount of solvent added to keep the total amount unchanged. The component contents of each embodiment and comparative example are shown in Table 1 below.

[0176] Table 1 Content of each component

[0177]

[0178]

[0179] The slurries obtained in Examples 1-17 and Comparative Examples 1-2 were cured on the ITO surface at 130° C. for 10 minutes under nitrogen conditions. The performance indicators are shown in Table 2, where:

[0180] The resistivity determination method is: use a square resistance meter commonly used in the art to test the square resistance of a 20mm*20mm square, use a film thickness meter commonly used in the art to test the thickness, input the software, and automatically calculate the resistivity.

[0181] The contact resistance is measured by using a conventional method in the art to test the resistance between two adjacent thin gate lines with a length of 15 mm and a width of 100 μm. The ITO square resistance does not exceed 60 mΩ / □.

[0182] The storage time is determined by testing the slurry viscosity every 5 days. If the viscosity exceeds 60% of the initial viscosity, the slurry is considered to be invalid.

[0183] Table 2 Slurry properties of different embodiments

[0184]

[0185]

[0186] As can be seen from the above examples, comparative example 1 uses imidazole as a promoter, which has the effect of promoting the polymerization of epoxy resin, but it has high activity and low stability. It will promote the gel reaction between epoxy resin and curing agent in a short time, and the viscosity will continue to increase during the printing process, resulting in the inability to produce continuously; comparative example 2 does not add a promoter, and its stability is good, but the degree of curing is very low under the temperature condition of 130°C, the resistivity is high, and the conductivity is low; the copper paste described in this application, due to the addition of a monosubstituted urea or disubstituted urea containing a bifunctional group as a promoter, its minimum deblocking temperature is 80°C, the paste can be stably stored before curing, and after deblocking, it can promote the rapid reaction of the curing agent and epoxy resin, and it is completely cured under nitrogen conditions at 130°C for 10min. After curing, the contact resistance and resistivity are relatively low, and the conductive performance is good. The conductive additive added to the copper paste described in this application can further reduce the contact resistance after curing. This application can achieve low-temperature curing of conductive copper paste, and the contact resistance and resistivity of the obtained low-temperature conductive copper paste are low, and the storage stability is good.

[0187] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.

Claims

1. A low temperature conductive copper paste, wherein: The low-temperature conductive copper paste comprises copper powder, polymer resin, solvent, curing agent and accelerator, wherein the accelerator is a monosubstituted urea or disubstituted urea containing a bifunctional group; The accelerator is DYHARD UR400 or DYHARD UR500; Calculated by mass percentage in the low-temperature conductive copper paste, the accelerator is 0.15-0.45%.

2. The low-temperature conductive copper paste according to claim 1, wherein: The low-temperature conductive copper paste contains a conductive auxiliary agent, and the conductive auxiliary agent is imidazole sulfonate or imidazole phosphate.

3. The low-temperature conductive copper paste according to claim 2, wherein: Calculated by mass percentage in the low-temperature conductive copper paste, the conductive auxiliary agent is 0.05-0.20%.

4. The low-temperature conductive copper paste according to any one of claims 1 to 3, wherein: The low-temperature conductive copper paste further comprises a dispersant, a coupling agent and a thixotropic agent.

5. The low-temperature conductive copper paste according to claim 4, wherein, in terms of mass percentage in the low-temperature conductive copper paste, The copper powder is 86-92%; The polymer resin is 1-3%; The solvent is 4-8%; The curing agent is 0.5-1.5%; The dispersant is 0.2-1%; The coupling agent is 0.2-0.5%; The thixotropic agent is 0.01-0.05%.

6. The low-temperature conductive copper paste according to any one of claims 1 to 3, wherein: The polymer resin comprises a main resin and an auxiliary resin.

7. The low-temperature conductive copper paste according to claim 6, wherein: The main resin is selected from one or more of hydrogenated bisphenol A epoxy resin, polyurethane modified epoxy resin, dimer acid modified epoxy resin and siloxane modified epoxy resin; And / or, the auxiliary resin is an aldehyde-ketone resin.

8. The low-temperature conductive copper paste according to claim 6, wherein: Calculated by mass percentage in the polymer resin, the main resin accounts for 60-90% and the auxiliary resin accounts for 10-40%.

9. The low-temperature conductive copper paste according to any one of claims 1 to 3, wherein: The copper powder comprises micron-sized flaky copper powder and nano-sized spherical copper powder.

10. The low-temperature conductive copper paste according to claim 9, wherein: Calculated by mass percentage in the copper powder, the micron-grade flaky copper powder accounts for 30-50%, and the nano-grade spherical copper powder accounts for 50-70%.

11. The low-temperature conductive copper paste according to any one of claims 1 to 3, wherein: The solvent is selected from one or more of dibasic acid ester (DBE), diethylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol butyl ether, diethylene glycol butyl ether acetate and terpineol.

12. The low-temperature conductive copper paste according to claim 4, wherein: The curing agent is selected from one or more of Trixene BI 7982, MF-K60X, ketoxime blocked isocyanate, hexanethiol blocked hexamethylene diisocyanate, and dodecyl mercaptan blocked diphenyl diisocyanate; and / or, the dispersant is selected from one or more of BYK-108, BYK-110, BYK-111, Tween 80, oleic acid, oleylamine and triethyl phosphate; And / or, the coupling agent is an organosilicon coupling agent and / or a titanate coupling agent; And / or, the thixotropic agent is polyamide wax, polyoxyethylene castor oil, hydrophobic gas silicone or BYK-405.

13. The low-temperature conductive copper paste according to claim 12, wherein: The organic silicon coupling agent is KH-560 and / or KH-570.

14. The low-temperature conductive copper paste according to claim 12, wherein: The titanate coupling agent is selected from one or more of isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and isopropyl tri(dioctyl phosphate acyloxy) titanate.

15. Use of low-temperature conductive copper paste in perovskite cells, wherein: The low-temperature conductive copper paste is used to make electrodes of perovskite cells, and the low-temperature conductive copper paste is the low-temperature conductive copper paste described in any one of claims 1-14.